Integrated Vector Management to Control Malaria During the Covid-19’s Pandemic in Lawang Kidul District - Maurend Yayank Lewinsca; Mursid Raharjo; Nurjazuli Nurjazuli (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Integrated Vector Management (IVM) is an effective effort to achieve malaria elimination. Reducing malaria cases in Indonesia still requires strategic steps to achieve the malaria elimination target in 2030. Lawang Kidul District is a priority area for malaria elimination in 2023 in Muara Enim Regency with an API value of 0,13). This study aims to analyze the application of Integrated Vector Management (IVM) in controlling malaria in the era of the COVID-19 pandemic in the Lawang Kidul District. The method used is a qualitative approach with in-depth interviews with informants from the health and government sectors. The results of the reference analysis of the NVivo 12 Pro coding show an integrated approach (126 codes), case-based decision making (37 codes), cross-sectoral cooperation (102 codes), advocacy for legislative mobilization (31 codes), and resource capacity (57 codes). Malaria Integrated Vector Management (IVM) efforts in Lawang Kidul District have not been maximized in several IVM elements such as assessing resource needs, preventing control efforts that are hampered due to the COVID-19 pandemic, community involvement in decision making, strengthening cross-sectoral commitments, policymaking, and policy implementation. Increased commitment to cross-sectoral advocacy, prioritizing the issue of malaria elimination, empowering mining communities, following up on village regulations, and making district-level policies are needed so that district-level malaria elimination can be achieved by 2023.  Abstrak: Integrated Vector Management (IVM) merupakan upaya efektif untuk mencapai eliminasi malaria. Penurunan kasus malaria di Indonesia tetap membutuhkan langkah-langkah strategis agar dapat mencapai target eliminasi malaria tahun 2030 mendatang. Kecamatan Lawang Kidul merupakan wilayah prioritas eliminasi malaria tahun 2023 di Kabupaten Muara Enim dengan nilai API 0,13. Penelitian ini bertujuan untuk menganalisis penerapan Integrated Vector Management (IVM) dalam pengendalian malaria pada era pandemi COVID-19 di Kecamatan Lawang Kidul. Metode yang digunakan pendekatan kualitatif dengan teknik wawancara mendalam pada informan yang berasal dari sektor kesehatan dan pemerintahan. Hasil analisis referensi koding NVivo 12 Pro menunjukkan elemen pendekatan terintegrasi (126 koding), pengambilan keputusan berdasarkan kasus (37 koding), kerjasama lintas sektor (102 koding), advokasi mobilisasi legislasi (31 koding), dan kapasitas sumber daya (57 koding). Upaya Integrated Vector Management (IVM) malaria di Kecamatan Lawang Kidul belum maksimal dibeberapa elemen IVM seperti penilaian kebutuhan sumber daya, upaya pencegahan pengendalian yang terhambat karena pandemi COVID-19, keterlibatan masyarakat dalam pengambilan keputusan, penguatan komitmen lintas sektor, pembuatan kebijakan dan implementasi kebijakan. Peningkatan komitmen advokasi lintas sektor, memprioritaskan masalah eliminasi malaria, memberdayakan masyarakat tambang, tindak lanjut kebijakan peraturan desa, dan pembuatan kebijakan tingkat kabupaten diperlukan agar eliminasi malaria tingkat kabupaten dapat tercapai pada tahun 2023.